The Innovation of the Thumbs Up Sakera Program (Recognizing Violence against Women and Children by Picking Up a Ball) in Pasuruan Regency - Ikhsan Setiawan; Lailul Mursyidah (Indonesian Journal of Public Policy Review, 2022)
In order to minimize the amount of violence in Pasuruan Regency, the Office of Family Planning and Women's Empowerment created an innovation that was realized in a program. The program is the Sakera Thumb program (Aware of Violence against Women and Children by Picking Up the Ball). The purpose of this study is to describe and analyze the innovation of the Sakera Thumb program in Pasuruan Regency. In this study, the research method used by the researcher is descriptive qualitative. In collecting data the researchers used interviews, observation, documentation. The results show that the innovation of the Sakera Thumb program has several unique features, namely the Sakera Thumb page, electronic thumb hotline card, thumb card, women and children protection car, and so on. Some of these unique features have made the Sakera Thumb program a top 99 public service innovation in 2017 and a participant in the united nations public service awards in 2018. In addition, the Sakera Thumb program innovation has become the answer to the problem of violence in Pasuruan Regency.